Integration of transthoracic focused cardiac ultrasound in the diagnostic algorithm for suspected acute aortic syndromes. (25th April 2019) - Nazerian, Peiman; Mueller, Christian; Vanni, Simone; Soeiro, Alexandre de Matos; Leidel, Bernd A; Cerini, Gabriele; Lupia, Enrico; Palazzo, Andrea; Grifoni, Stefano; Morello, Fulvio
Abstract: Aims: The diagnosis of acute aortic syndromes (AASs) is challenging and requires integrated strategies. Transthoracic focused cardiac ultrasound (FoCUS) is endorsed by guidelines as a first-line/triage tool allowing rapid bedside assessment of the aorta. However, the performance of FoCUS in the European Society of Cardiology-recommended workup of AASs awaits validation. Methods and results: This was a prespecified subanalysis of the ADvISED multicentre prospective study. Patients with suspected AAS underwent FoCUS for detection of direct/indirect signs of AAS. Clinical probability assessment was performed with the aortic dissection detection risk score (ADD-RS). Case adjudication was based on advanced imaging, surgery, autopsy, or 14-day follow-up. An AAS was diagnosed in 146 (17.4%) of 839 patients. Presence of direct FoCUS signs had a sensitivity and specificity of 45.2% [95% confidence interval (CI) 37–53.6%] and 97.4% (95% CI 95.9–98.4%), while presence of any FoCUS sign had a sensitivity and specificity of 89% (95% CI 82.8–93.6%) and 74.5% (95% CI 71–77.7%) for AAS. The additive value of FoCUS was most evident within low clinical probability (ADD-RS ≤1). Herein, direct FoCUS signs were identified in 40 (4.8%) patients ( P < 0.001), including 29 with AAS. ADD-RS ≤1 plus negative FoCUS for AAS rule-out had a sensitivity of 93.8% (95% CI 88.6–97.1%) and a failure rate of 1.9% (95% CI 0.9–3.6%). Addition of negative D-dimer led to a failure rate of 0% (95% CI 0–1.2%). Conclusion: FoCUS has additive value in the workup of AASs. Direct FoCUS signs can rapidly identify patients requiring advanced imaging despite low clinical probability. In integrated bundles, negative FoCUS is useful for rule-out of AASs.